2007
DOI: 10.1177/0363546507301661
|View full text |Cite
|
Sign up to set email alerts
|

Can a Double-Row Anchorage Technique Improve Tendon Healing in Arthroscopic Rotator Cuff Repair?

Abstract: In this first study comparing double- and single-row anchorage techniques, we found no significant difference in clinical results, but tendon healing rates were better with the double-row anchorage. Improvements in the double-row technique might lead to better clinical and tendon healing results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(80 citation statements)
references
References 29 publications
7
72
0
1
Order By: Relevance
“…In contrast, Park et al [48] reported that in patients with large to massive tears (> 3 cm), the American Shoulder and Elbow Surgeons Score, Constant scores and Shoulder Strength Index were all significantly better in the group that had double-row repair. Despite the fact that most studies have failed to demonstrate clinical differences with singe vs double row repairs at short term follow-up, there appears to be a lower re-tear rate for the double-row compared with the single-row repairs [49][50][51] . Lapner et al [49] , in a multicenter randomized controlled trial comparing single-row with double-row fixation in arthroscopic rotator cuff repairs reported that although doublerow fixation was associated with higher healing rates, no significant differences in functional or quality-oflife outcomes were identified between single-row and double-row fixation techniques.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 88%
“…In contrast, Park et al [48] reported that in patients with large to massive tears (> 3 cm), the American Shoulder and Elbow Surgeons Score, Constant scores and Shoulder Strength Index were all significantly better in the group that had double-row repair. Despite the fact that most studies have failed to demonstrate clinical differences with singe vs double row repairs at short term follow-up, there appears to be a lower re-tear rate for the double-row compared with the single-row repairs [49][50][51] . Lapner et al [49] , in a multicenter randomized controlled trial comparing single-row with double-row fixation in arthroscopic rotator cuff repairs reported that although doublerow fixation was associated with higher healing rates, no significant differences in functional or quality-oflife outcomes were identified between single-row and double-row fixation techniques.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 88%
“…Charousset et al [5] conducted a non-randomised comparative study including 31 patients in the double-row group and 35 in the single-row group. No significant differences were found regarding clinical outcomes measured by the Constant scale with a follow-up of approximately 28 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, the technique using a double row of anchors is reported to re-establish the normal rotator cuff footprint and increase the contact area for healing [8,13,23] making the anatomical and biomechanical outcomes are better than with the single-row technique [3,6,15,18]. Although a few studies have compared single-row repair and double-row repair with regard to clinical aspects [5,7,17,19,21,24], no articles have been published that support the superior clinical outcomes of double-row fixation over single-row fixation. This prospective randomised clinical trial was performed to address the question of whether a double-row rotator cuff anchor repair gives results superior to a single-row anchor repair in clinical outcome scores and in magnetic resonance imaging (MRI) evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…8 Charousset et al also found no significant difference in clinical results; but, anatomic tendon healing rates were better with the double row repairs based on computed tomographic (CT) arthrography. 13 Several tears 3 cm were repaired using a double row technique, they had better American Shoulder and Elbow Surgeons (ASES) and Constant scores postoperatively as compared to single row repairs. This was the first study to show a clinical difference between single and double row repairs, and it was strictly in these larger sized tears.…”
Section: Clinical Datamentioning
confidence: 99%